BIO-EFFICACY OF THE ESSENTIAL OIL OF THYMUS VULGARIS AGAINST DERMESTES MACULATUS DEGEER 1774 (COLEOPTERA: DERMESTIDAE) INFESTING SMOKE-DRIED CLARIAS GARIEPINUS BURCHELL 1822 - A. Nasiru; M Suleiman; B. Absulkarim (The Bioscientist, 2022)
Increase in demand for an alternative to conventional pesticides, resulted in testing various plants materials against different storage pests. In this study, white thyme (Thymus vulgaris L) essential oil (TEO) obtained by steam distillation using Clevenger apparatus was evaluated against two developmental stages of Dermestes maculatus by residual contact method under laboratory conditions (260C ±20C and 75% ±3% RH). Four concentrations (2.5%, 5%, 7.5% and 10%) of TEO were separately applied on fifteen grams of C. gariepinus. Newly emerged adults and 3rd instar larvae of the pest were exposed to the treated samples for a period of five days. Results showed that the TEO had significant (P< 0.05) effect on both adult and larval mortalities which was concentrations and time of exposure dependent. It was recorded that 7.5% and 10% concentrations resulted in 40% and 50% larval mortality of Dermestes maculatus48 HAE. Meanwhile 70% and 90% mortalities were observed in the same concentrations at 72 and 96HAE, respectively. On the other hand, adults were more susceptible than the larvae whereby higher (80% and 90%) mortalities were recorded within 24HAEin 7.5% and 10% concentrations, and complete(100%) adult mortality was observed at 48 HAE, respectively at the same concentrations. The LC50 of TEO against adults D. maculatus at 24 hours is 5.71% and against larvae is 13.93% with LT50 of 9.63h at 10% concentration against adult and 43.87h against larvae at the same concentration. Therefore, TEO can be used as an alternative to synthetic pesticides in the control of Dermestes maculatus infestations.